Subterranean termite phylogeography reveals multiple postglacial colonization events in southwestern Europe. Issue 16 (27th July 2016) - Lefebvre, Thomas; Vargo, Edward L.; Zimmermann, Marie; Dupont, Simon; Kutnik, Magdalena; Bagnères, Anne‐Geneviève
Abstract: A long‐standing goal of evolutionary biology is to understand how paleoclimatic and geological events shape the geographical distribution and genetic structure within and among species. Using a diverse set of markers (cuticular hydrocarbons, mitochondrial and nuclear gene sequences, microsatellite loci), we studied Reticulitermes grassei and R. banyulensis, two closely related termite species in southwestern Europe. We sought to clarify the current genetic structure of populations that formed following postglacial dispersal from refugia in southern Spain and characterize the gene flow between the two lineages over the last several million years. Each marker type separately provided a fragmented picture of the evolutionary history at different timescales. Chemical analyses of cuticular hydrocarbons and phylogenetic analyses of mitochondrial and nuclear genes showed clear separation between the species, suggesting they diverged following vicariance events in the Late Miocene. However, the presence of intermediate chemical profiles and mtDNA introgression in some Spanish colonies suggests ongoing gene flow. The current genetic structure of Iberian populations is consistent with alternating isolation and dispersal events during Quaternary glacial periods. Analyses of population genetic structure revealed postglacial colonization routes from southern Spain to France, where populations underwent strong genetic bottlenecks after traversing the Pyrenees resulting in parapatric speciation. Abstract : Phylogeography of termites in southwestern Europe revealed postglacial colonization routes from southern Spain to France, where populations underwent strong genetic bottlenecks after traversing the Pyrenees resulting in parapatric speciation.